Biochemical characterization of a low molecular weight aspartic protease inhibitor from thermo-tolerant bacillus licheniformis: kinetic interactions with pepsin - Kumar, Ajit; Rao, Mala (Biochimica et Biophysica Acta-General Subjects, 2006)
The present article reports a low molecular weight aspartic protease inhibitor, API, from a newly isolated thermo-tolerant Bacillus licheniformis. The inhibitor was purified to homogeneity as shown by rp-HPLC and SDS-PAGE. API is found to be stable over a broad pH range of 2-11 and at temperature 90 degrees C for 2 1/2 h. It has a Mr (relative molecular mass) of 1363 Da as shown by MALDI-TOF spectra and 1358 Da as analyzed by SDS-PAGE The amino acid analysis of the peptide shows the presence of 12 amino acid residues having Mr of 1425Da. The secondary structure of API as analyzed by the CD spectra showed 7% alpha-helix, 49% beta-sheet and 44% aperiodic structure. The Kinetic studies of Pepsin-API interactions reveal that API is a slow-tight binding competitive inhibitor with the IC(50) and K(i) values 4.0nM and (3.83 nM - 5.31 nM) respectively. The overall inhibition constant K(i)* value is 0.107 +/- 0.015 nM. The progress curves are time-dependent and consistent with slow-tight binding inhibition: E+I reversible arrow (k(4), k(5)) EI reversible arrow (k(6), k(7)) EI*. Rate constant k(6) = 2.73 +/- 0.32 s(-1) reveals a fast isomerization of enzyme-inhibitor complex and very slow dissociation as proved by k(7)=0.068 +/- 0.009s(-1). The Rate constants from the intrinsic tryptophanyl fluorescence data is in agreement with those obtained from the kinetic analysis; therefore, the induced conformational changes were correlated to the isomerization of EI to EI*. (c) 2006 Elsevier B.V. Ail rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; enzyme kinetic; Pepsin; Slow-tight binding inhibition

Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles

Biochemical characterization of a novel beta-1-3, 1-4 glucan 4-glucanohydrolase from thermomonospora sp having a single active site for lichenan and xylan - Anish, Ramakrishnan; Rao, Mala (Biochimie, 2007)
A bifunctional high molecular weight (Mr, 64,500 Da) beta-1-3, 1-4 glucan 4-glucanohydrolase was purified to homogeneity from Thermomonospora sp., exhibiting activity towards lichenan and xylan. A kinetic method was used to analyze the active site that hydrolyzes lichenan and xylan. The experimental data was in agreement with the theoretical values calculated for a single active site. Probing the conformation and microenvironment at active site of the enzyme by fluorescent chemo-affinity label, OPTA resulted in the formation of an isoindole derivative with complete inactivation of the enzyme to hydrolyse both lichenan and xylan confirmed the results of kinetic method. OPTA forms an isoindole derivative by cross-linking the proximal thiol and amino groups. The modification of cysteine and lysine residues by DTNB and TNBS respectively abolished the ability of the enzyme to form an isoindole derivative with OPTA, indicating the participation of cysteine and lysine in the formation of isoindole complex. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1-4 glucan 4-glucanohydrolase; beta-1-3; bifunctional; O-phthaialdehyde; single active site; Thermomonospora sp.; Xylanase

Biochemical characterization of an aspartic protease from vigna radiata: kinetic interactions with the classical inhibitor pepstatin implicating a tight binding mechanism - Kulkarni, Aarohi; Rao, Mala (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2007)
{Aspartic proteases are the focus of recent research interest in understanding the physiological importance of this class of enzymes in plants. This is the first report of an aspartic protease from the seeds of Vigna radiata. The aspartic protease was purified to homogeneity by fractional ammonium sulfate precipitation and pepstatin-A agarose affinity column. It was found to have a molecular weight of 67,406 Da by gel filtration chromatography. SDS-PAGE analysis revealed the presence of a heterodimer with subunits of molecular weights of 44,024 and 23,349 Da respectively. The enzyme was pH stable with the amino acid analysis confirming the molecular weight of the protein. The substrate cleavage site as analyzed by using the synthetic substrate was found to be the Phe-Tyr bond. The kinetic interactions of the enzyme were studied with the universal inhibitor, pepstatin A. This is the first report on the interactions of a plant aspartic protease with pepstatin-A, an inhibitor from a microbial source. A competitive one-step mechanism of binding is observed. The progress curves are time-dependent and consistent with tight binding inhibition. The K(i) value of the reversible complex of pepstatin with the enzyme was 0.87 mu M whereas the overall inhibition constant K(i)*
Keywords: ant colony; global optimization; metaheuristics; multimodal continuous functions; particle swarm optimization

Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Bioethanol production from renewable polymer lichenan using lichenase from an alkalothermophilic thermomonospora sp and thermotolerant yeast - Menon, Vishnu; Divate, Rupesh; Rao, Mala (Fuel Processing Technology, 2011)
Biomass feedstocks available decentrally will be more commodious for localized biorefinery approach than the exhaustive large scale and centralized plants driven by cost intensive technology. Lichen is present in a wide range of habitats in a distributed manner. A maximum hydrolysis of 73%-76% for lichenan from Cetraria islandica, Usnea barbata and Parmelia sp. were obtained in 24 h using lichenase from an alkalothermophilic Thermomonospora sp. wherein the hydrolysis was 100% with commercial enzyme Accellerase (TM) 1000. The synergistic role of beta-glucosidase in lichenan hydrolysis was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora lichenase which resulted in complete hydrolysis. The hydrolysates of lichenan obtained using Accellerase or a cocktail of Thermomonospora lichenase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.45 g/g-0.48 g/g with theoretical conversion efficiencies of 93%-96%. The Ca-alginate immobilized yeast cells were reused eight times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrolysis; Lichenan; Lichenase; Synergism; Thermotolerant yeast

Biochemical characterization of a novel thermostable xyloglucanase from an alkalothermophilic thermomonospora sp. - Pol, Dipali; Menon, Vishnu; Rao, Mala (Extremophiles, 2012)
Xyloglucanase from an extracellular culture filtrate of alkalothermophilic Thermomonospora sp. was purified to homogeneity with a molecular weight of 144 kDa as determined by SDS-PAGE and exhibited specificity towards xyloglucan with apparent K (m) of 1.67 mg/ml. The enzyme was active at a broad range of pH (5-8) and temperatures (40-80A degrees C). The optimum pH and temperature were 7 and 70A degrees C, respectively. The enzyme retained 100% activity at 50A degrees C for 60 h with half-lives of 14 h, 6 h and 7 min at 60, 70 and 80A degrees C, respectively. The kinetics of thermal denaturation revealed that the inactivation at 80A degrees C is due to unfolding of the enzyme as evidenced by the distinct red shift in the wavelength maximum of the fluorescence profile. Xyloglucanase activity was positively modulated in the presence of Zn2+, K+, cysteine, beta-mercaptoethanol and polyols. Thermostability was enhanced in the presence of additives (polyols and glycine) at 80A degrees C. A hydrolysis of 55% for galactoxyloglucan (GXG) from tamarind kernel powder (TKP) was obtained in 12 h at 60A degrees C and 6 h at 70A degrees C using thermostable xyloglucanases, favouring a reduction in process time and enzyme dosage. The enzyme was stable in the presence of commercial detergents (Ariel), indicating its potential as an additive to laundry detergents.
Keywords: Alkalothermophilic Thermomonospora sp.; Biotechnological applications; Purification; Thermostable; Xyloglucanase